Sensory properties of supercritical CO2 fractions extracted from Magnum hop essential oil. Issue 3 (22nd June 2020) - Dietz, Christina; Cook, David; Wilson, Colin; Marriott, Ray; Ford, Rebecca
Abstract : Hop oil fractions with unique sensory characteristics can be extracted from hop essential oil using green solvents such as supercritical (sc) CO2 . These extracts meet clean label requirements and can be used to manage fluctuations in volatile composition caused by global warming. A sensory descriptive analysis approach was applied to assess the sensory profiles of Magnum hop oil and five scCO2 fractions. Ten sensory panellists were trained and used to establish an attribute lexicon. All samples, a control, and an experimental replicate were evaluated at 800 μg/L in ethanol (4% abv) in triplicate. Data were analysed by three‐factor Analysis of Variance (ANOVA) and Tukey's test (HSD). Volatile compounds were determined using gas chromatography‐mass spectrometry (GC‐MS). Relationships between the volatile compounds and sensory profiles were analysed using Principal Component Analysis (PCA) and Partial Least Squares (PLS) regression. In contrast to the majority of fractions, the total oil (the most complex sample) and the sesquiterpene fraction (as the largest chemical group in the total oil) were not described by any key sensory attributes. This illustrates the advantage of hop oil fractionation to pull out specific sensory characteristics. The β ‐myrcene in the myrcene fraction induced an intense 'crushed grass, sap' aroma while the fractions containing several geranyl and methyl esters and ketones were characterised by fruity‐ and floral‐type aroma and flavour attributes. Interestingly, the most polar fraction comprising of terpene alcohols delivered a complex sensory experience by adding sweetness. Moreover, a trigeminal 'peppery tingling' sensation was detected, which is likely to be caused by sensory interactions. © 2020 The Authors. Journal of the Institute of Brewing published by John Wiley & Sons Ltd on behalf of The Institute of Brewing & Distilling